Measuring anti-transgender stigma in low-income and middle-income countries: a scoping review protocol - Clare Barrington; Jennifer Toller Erausquin; Amanda E Tanner; Tamar Goldenberg; Sulianie Mertus; Mohammed Sheikh Eldin Jibriel (BMJ Open)
Introduction Globally, transgender and other gender diverse (trans) people face pervasive stigma, which contributes to health inequities across multiple health outcomes. Stigma is a fundamental cause of health inequities because it simultaneously limits access to resources, contributes to systemic vulnerability and generates chronic stress. Anti-trans stigma occurs across multiple socioecological levels, resulting in multiple possible definitions and measurements of trans stigma. Understanding how trans stigma has been measured in low-income and middle-income countries (LMICs) is critical to health promotion efforts for trans communities. Accordingly, this scoping review will identify and examine how anti-trans stigma has been measured in existing LMIC-specific research to inform best practices for measurement of anti-trans stigma that includes consideration of local context.Methods and analysis This is the protocol for a scoping review of anti-trans stigma in LMICs. We will search (from January 2001 to December 2021) PubMed, WHO Global Medicus and EBSCO. Study selection will conform to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews Checklist. Original studies in English, Spanish, Arabic or Russian will be included. Reviewers will independently screen all citations, full-text articles and abstract data. Data analysis will involve quantitative and qualitative methods. A narrative summary of findings will be conducted.Ethics and dissemination As a scoping review (no direct interaction with participants), this study is exempt from human subjects oversight. Understanding context-specific ways to measure anti-trans stigma is urgently needed to support trans health globally. The planned scoping review will help to address this gap. Results of the review will be disseminated in a peer-reviewed journal and likely in other media such as conferences, seminars and symposia.Protocol registration number osf.io/qcs2v